Enhancing Students Anti-Corruption Awareness through a QR Code-Supported Problem-Based Learning Model - Etin Solihatin; Raharjo Raharjo; Marsofiyati Marsofiyati; Roby Ibnu Syarifain; Ricky Rasyid; Randy Rahman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This study aimed to develop a problem-based learning model integrating anti-corruption values supported by QR Code-assisted teaching materials and to examine its feasibility and effectiveness. The study employed a research and development (R&D) approach based on the Dick and Carey model. The effectiveness of the developed model was evaluated using a one-group pretest–posttest design involving 50 students. The resulting learning model consists of five stages: (1) analysis of needs and student characteristics; (2) identification of real-world problems guided by educators; (3) selection of significant problems for solution exploration; (4) determination of the most feasible solution supported by scientific reasoning; and (5) presentation and dissemination of the selected solution. Expert validation involving material, language, and design experts indicated that the model was highly feasible, with an average score of 4.66, while small-group testing yielded a score of 4.74. The effectiveness analysis showed that the mean posttest score (M = 90.34, SD = 5.02) was substantially higher than the mean pretest score (M = 60.04, SD = 5.45). The mean difference was 30.30 points (95% CI [29.81, 30.79]), with a very large effect size (Cohen’s d ≈ 5.8). These results indicate that the developed learning model is both feasible and highly effective in improving students’ learning outcomes while supporting the development of problem-solving skills and collaborative learning.